Conflict Potential of the Rohingya People in Bangladesh and Beyond - MD Rafiqul Islam; Umme Wara (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2022)
The article addresses how Myanmar's Rohingya conflict could generate a potential for conflict within the borders of Bangladesh and beyond. The conflict in Myanmar due to the Rohingyas being deprived of their national citizenship had led to the mass exodus in 2017 to Bangladeshi land and the subsequent conflict in the host place. It was referred to various situations, including disputes, killing, abduction, and tensions between the refuges and host people. Based on existing theories of ‘exporting conflict’ such as displacing conflict and spill over effect of ethnic conflict, the article attempted to show how the Rohingya conflict originated in Myanmar lead to serious conflicts taking place in Bangladesh. The theoretical basis proposed in the article had been supported with reliable secondary sources of information and published expert opinions on the contemporary situation of the temporary Rohingya settlements in Bangladesh with regards to their sheltering, refugee management, and progress towards their repatriation process to Myanmar. The article argued that Myanmar's civil conflict had spilled over into Bangladesh's borders due to a sequence of events starting from when Myanmar's civil conflict erupted from its National Citizenship Act. Findings suggest that the Myanmar conflict has been displaced to Bangladesh through many refugee settlements that puts Bangladesh's population in midst of a host of issues concerning livelihood, safety, and security. This has been done while touching upon Bangladesh's position as a host country to millions of Rohingya refugees and shouldering issues already stemming from the temporary shelter of Rohingya people within its borders.